Pengaruh Penerapan SIA, Kecanggihan Teknologi Informasi dan Komitmen Organisasi Terhadap Kinerja Karyawan pada LPD Kecamatan Marga - Putu Dicky Ari Pratama; I Ketut Puja Wirya Sanjaya; I Gusti Ayu Intan Saputra Rini (Universitas Warmadewa, 2023)
This study aims to prove the effect of the effectiveness of implementing accounting information systems, information technology sophistication, and organizational commitment on employee performance at Village Credit Institutions (LPD) in Marga District. Determination of the sample in this study using the purposive sampling method so that a total sample of 66 respondents was obtained. The data collection technique used a questionnaire, with a Likert scale and before distributing it, the research instrument was tested first. The collected data was processed using multiple linear regression analysis techniques. The results of the study prove that: (1) the effectiveness of implementing accounting information systems has a positive effect on employee performance, (2) information technology sophistication has a positive effect on employee performance and (3) organizational commitment has no effect on employee performance.